2005
DOI: 10.3386/w11074
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Defaults and Active Decisions

Abstract: Defaults can have a dramatic influence on consumer decisions. We identify an overlooked but practical alternative to defaults: requiring individuals to make an explicit choice for themselves. We study such "active decisions" in the context of 401(k) saving. We find that compelling new hires to make active decisions about 401(k) enrollment raises the initial fraction that enroll by 28 percentage points relative to a standard opt-in enrollment procedure, producing a savings distribution three months after hire t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
323
2
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(339 citation statements)
references
References 10 publications
(16 reference statements)
11
323
2
3
Order By: Relevance
“…The opt-out policy (i.e., requiring online users to explicitly request their exclusion from further contacting lists) is more effective in capturing consumers' agreement for further online contact compared to the opt-in policy (Johnson et al 2002). Yet Agnew et al (2008) failed to confirm the power of defaults in annuity choice, while Carroll et al (2009) claim that depending on the conditions, different default policies may engage higher compliance rates.…”
Section: Default Policies For Greening Servicesmentioning
confidence: 87%
See 3 more Smart Citations
“…The opt-out policy (i.e., requiring online users to explicitly request their exclusion from further contacting lists) is more effective in capturing consumers' agreement for further online contact compared to the opt-in policy (Johnson et al 2002). Yet Agnew et al (2008) failed to confirm the power of defaults in annuity choice, while Carroll et al (2009) claim that depending on the conditions, different default policies may engage higher compliance rates.…”
Section: Default Policies For Greening Servicesmentioning
confidence: 87%
“…Although the power of the opt-out policy seems to capture higher levels of consumer compliance with the desired option, its superiority is still debatable, and scholars call for further evidence (Carroll et al 2009;Keller et al 2011). Johnson and Goldstein (2003) showed that the opt-out policy results in almost twice as high organ donation rates compared to the opt-in policy, while actual participation in organ donation programs is also significantly higher in countries that apply the presumed consent policy (i.e., opt-out) compared to participation rates in countries that apply the opt-in policy.…”
Section: Default Policies For Greening Servicesmentioning
confidence: 98%
See 2 more Smart Citations
“…m R 1 can not solve the optimal contribution rate. 14 We need to use the value function itself to search the optimal contribution rate numerically. …”
Section: A23 Optimize Contribution Ratementioning
confidence: 99%